Nine-fold higher risk of acute myocardial infarction in subjects with type 1 diabetes compared to controls in Norway 1973–2017 - Saeed, Maryam; Stene, Lars C.; Ariansen, Inger; Tell, Grethe S.; Tapia, German; Joner, Geir; Skrivarhaug, Torild (Cardiovascular diabetology, 2022)
We aimed to study the cumulative incidence and risk factors (sex, age, calendar year of diabetes onset, country of origin and educational level) of acute myocardial infarction (AMI) in subjects with type 1 diabetes and matched controls. A nationwide cohort of subjects with type 1 diabetes diagnosed at age < 15 years in Norway during 1973-2000 was followed until the first AMI event, emigration, death or 31st of December 2017. The Norwegian Childhood Diabetes Registry was linked to five nationwide registries, and up to ten sex- and age-matched controls per case were included. Among 7086 subjects with type 1 diabetes, 170 (2.4%) were identified with incident AMI, compared to 193 (0.3%) of 69,356 controls. Mean age and diabetes duration at first AMI was 40.8 years and 30.6 years, respectively. The probability of AMI after 40 years of follow-up was 8.0% in subjects with type 1 diabetes and 1.1% in controls, aHR 9.05 (95% CI 7.18-11.41). In type 1 diabetes, male sex (aHR 1.45), higher age at onset of diabetes and lower education (higher compared to lower, aHR 0.38) were significantly associated with higher risk of AMI. There was no significant time trend in AMI by calendar year of diabetes onset. We found nine-fold excess risk of AMI in subjects with type 1 diabetes, and three-fold higher risk in subjects with low versus high education. These results highlight a strengthened focus on prevention of cardiovascular disease, and diabetes education tailored to the subjects' educational background.